The borders of justice - Balibar, Étienne, 1942-; Mezzadra, Sandro; Samāddāra, Raṇabīra (Politics, history, and social change., 2012)
International in scope and featuring a diverse group of contributors, The Borders of Justice investigates the complexities of transitional justice that emerge from its "social embeddedness." This original and provocative collection of essays, which stem from a collective research program on social justice undertaken by the Calcutta Research Group, confronts the concept and practices of justice. The editors and contributors question the relationship between geography, methodology, and justice-how and why justice is meted out differently in different places. Expanding on